Arsenic - Analytical and Toxicological Studies - Margarita Stoytcheva; Roumen Zlatev (IntechOpen, 2018)
Arsenic - Analytical and Toxicological Studies is a collection of original works focused on arsenic occurrence and chemistry, methods for arsenic determination and removal and arsenic toxicity and health risks. The most commonly used techniques for arsenic quantification and speciation, such as atomic absorption spectrometry, inductively coupled plasma-mass spectrometry, and inductively coupled plasma-emission spectrometry, among others, and the various procedures applied for arsenic separation and removal are exhaustively described. The mechanism of arsenic-induced toxicology, involving arsenic interaction with critical thiols in proteins and the health risks associated with exposure to arsenic, is also discussed.
English
Keywords: Physical Sciences; Engineering and Technology; Chemistry; Bioinorganic Chemistry; Inorganic Chemistry